Modulation of viral replication, autophagy and apoptosis by induction and mutual regulation of transcription factors EB and E3 during coronavirus infection - Yang, Bei; Fung, To Sing; Yuan, Lixia; Chen, Rui Ai; Liu, Ding Xiang (Frontiers in Microbiology, 2025)
Viral invasion and replication in cells significantly impact lysosome structure and function. By sensing changes in the lysosome status, cascades of cellular responses are triggered to maintain lysosomal homeostasis. Two key regulators, transcription factors EB (TFEB) and E3 (TFE3), play essential regulatory roles in these processes by shuttling between the cytoplasm and the nucleus. In this study, we report that infection of cells and/or chickens by gammacoronavirus infectious bronchitis virus (IBV), human betacoronavirus OC43 (HCoV-OC43), and alphacoronavirus porcine epidemic diarrhea virus (PEDV) upregulates the expression of TFEB/TFE3 as well as their downstream targets, and induces the lysosomal stress response. Knockdown of TFE3 alone or together with TFEB demonstrated a pronounced role played by TFE3 in regulating viral replication, virus-induced autophagy and apoptosis in cells infected with the three viruses, and a synergistic effect of TFEB and TFE3 in cells infected with IBV and HCoV-OC43. Furthermore, inhibition of the biosynthetic secretory pathway with brefeldin A (BFA) demonstrated that the release of HCoV-OC43 is mainly via the lysosomal pathway. This study provides novel insights into the functional roles of the lysosomal biogenesis and stress response in coronavirus replication and virus-host interactions.